The role of podcasts in shaping cultural identity in Saudi Arabia (The International Journal of Educational Sciences and Arts, 2026)
This study aims to examine the role of podcasts in shaping cultural identity in Saudi Arabia amid the rapid transformations brought about by communication technologies and digital media. The study is grounded in a central research problem: the increasing reliance of audiences, particularly young people, on podcasts as a contemporary media platform that combines knowledge, entertainment, audio storytelling, and cultural interaction. This makes podcasting a potentially influential medium in shaping the components of cultural identity, including language, values, heritage, belonging, and social traditions.The study adopts a descriptive-analytical approach, using a questionnaire as the main tool for data collection from a simple random sample of active podcast listeners. It seeks to measure patterns of podcast use, the extent to which audiences depend on podcasts as a source of cultural content, and the impact of exposure to podcast content on cultural awareness and identity formation. The study is theoretically grounded in the Uses and Gratifications Theory and Cultivation Theory. The former explains audience motivations for using podcasts and the cognitive, emotional, and social gratifications derived from them, while the latter explains the cumulative influence of repeated exposure to audio content in reinforcing cultural values and shaping perceptions of identity.The significance of this study lies in its focus on podcasting as an emerging form of digital media capable of supporting Saudi cultural identity in the face of digital globalization and transnational media content. The study contributes to a deeper understanding of how podcasts can enhance cultural awareness, reinforce social and human values, and create space for dialogue and interaction between individuals and society. Its findings may also help guide the development of culturally relevant podcast content that speaks to young audiences through a contemporary digital language while preserving authenticity, belonging, and cultural continuity.
Keywords: Podcasting; Cultural Identity; Digital Media; Saudi Youth; Cultural Awareness; Uses and Gratifications Theory; Cultivation Theory; Saudi Culture